Language Patterns on Music Festival Posters from the 80s Era to the 2020s Era - Novita Puspahaty; Putri Rahmawati (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2024)
Differences in eras can affect language patterns in naming posters at music festivals. This study aimed to discover the differences in language patterns in music festival posters from the 80s to the 2020s. At the morphological level, we used Yule's theory (2010) to analyze word formation. Then, at the syntactic level, we used Morley's theory (2000) to examine phrases. We also used a content analysis to examine data collected from newspapers and social media. The results of the study showed that at the morphological level, the most commonly used in naming music festival titles from the 80s to the 2020s is the type of word borrowing and clipping. The borrowing word formation type is used up to 18 times, while the clipping word formation type is used 6 times. In addition, at the syntactic level, the results found are included in the category of noun phrase types from the 80s to the 2020s.